2008
DOI: 10.1111/j.1365-2206.2008.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge of caring: revisiting the need for knowledge support of carers

Abstract: A B S T R AC TFoster carers' knowledge of caring for abused and neglected children is a largely under-researched area. We know very little about the nature of carers' knowledge in relation to caring for children who have been abused or neglected. This paper reports on an exploratory study which examined the knowledge of caring. Qualitative data were analysed based on in-depth interviews with 10 foster carers in Queensland, Australia. A range of knowledge was identified showing an interaction of both personaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…There are calls for greater attention to the training and support needs of carers, their wellbeing and retention to caring [36, 37]. Many carers report high levels of stress and poor coping [3638].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are calls for greater attention to the training and support needs of carers, their wellbeing and retention to caring [36, 37]. Many carers report high levels of stress and poor coping [3638].…”
Section: Introductionmentioning
confidence: 99%
“…Many carers report high levels of stress and poor coping [3638]. Irrespective of their capacity to identify mental ill-health, many do not gain access to mental health care for the young person [39, 40].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, there has been a significant rise in the rate of children and young people placed in out-of-home care in Australia (AIHW 2007). There are many and varied reasons why children and young people are placed in out-of-home care; however, the majority of individuals are placed in care as a result of significant abuse and neglect (Osmond, Scott & Clark 2008). As a result of such abuse and neglect, many children and young people in out-of-home care experience significant trauma and associated mental health problems that can impact upon their psychological and emotional functioning (Larmar & Clark 2009;Sawyer, Carbone, Searle & Robinson 2007;Tarren-Sweeney & Hazel 2006).…”
Section: Out-of-home Care In Australiamentioning
confidence: 99%
“…Such stresses, as well as a range of factors that place the individual at greater risk of ongoing social and behavioural difficulties (e.g. insecure attachment, an unsafe home environment, poor social skills development), may negatively impact upon the child or young person's behaviour (AIHW 2006;Osmond, Scott & Clark 2008).…”
mentioning
confidence: 99%
“…With the rise in children and young people entering out-of-home care contexts in Australia (AIHW 2006), the need for greater support to carers and other health professionals is paramount (Butcher 2004;Carter 2002) (for a further elaboration of the Australian context, see Larmar & Clark 2009a). The needs of children and adolescents in the welfare system are varying, but many present with a range of complex issues that are influenced by histories of trauma, abuse and neglect (Osmond, Scott & Clark 2008). More recent studies have reported high incidences of drug and alcohol abuse (Ainsworth & Summers 2001), domestic violence (Kohl, Edleson, English & Barth 2005), mental illness (Phillips 2009), poverty and its associated effects (Thomson 2003) and poor attachment (AIHW 2006) in families of children and young people entering out-of-home care.…”
mentioning
confidence: 99%